More than just one labor market cycle in Germany? An analysis of regional unemployment data - Jens Boysen-Hogrefe; Markus Pape (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
We analyze unemployment dynamics for Germany on a regional basis by means of an approximate factor model. We first estimate the number of factors corresponding to the number of cycles. At least for the pre-'Hartz' reform data we find strong evidence for more than just one dynamic labor market cycle present in German regions. Thus, labor market dynamics are driven by more than a single nationwide business cycle. Next, we look for regional partitions reflecting the different cycles best. Our results indicate pronounced differences between East and West Germany for 1997 to 2004 and ongoing but reduced differences between 2005 and 2010. A convergence process is found to have taken place up until late 2001. There is evidence for the differences observed before 2004 to be driven by active labor market policy, which thus had a volatility-increasing effect on the labor market.
Keywords: C23; E24; E32; J08; 330; Arbeitslosigkeit; regionale Verteilung; Arbeitslosigkeitsentwicklung - Determinanten; Hartz-Reform - Auswirkungen; regionaler Vergleich; ökonomische Faktoren; Konjunkturabhängigkeit; institutionelle Faktoren; Arbeitsmarktpolitik; Ostdeutschland; Westdeutschland; Bundesrepublik Deutschland